A NOVEL DATA SECURITY : SECURE AND EXPRESSIVE CLOUD STORAGE DATA ACCESS CONTROL (International Journal of Food and Nutritional Sciences, 2021)
A growing idea in cloud administration, secure distributed storage intends to ensure the categorization of appropriated information while still giving flexible information access to cloud customers whose information is not under their physical control. This is accomplished by ensuring that only the information that has been appropriated is categorized. CP-ABE, which stands for cypher text-policy attribute-based encryption, is one of the most promising approaches for verifying the administration's certification. It is possible that the use of CP-ABE might result in an inevitable security breach that is referred to as the abuse of access accreditation (for instance, decoding privileges). This is due to the inherent "win big or bust" unscrambling factor that is inherent to CP-ABE. This article focuses on two significant examples in which a semi-trusted expert exploits the access qualification of a cloud client with malicious intent. As a potential solution to the problem of system exploitation, it is recommended that a distributed storage platform known as CryptCloud+ that has white-box discernibility and review be implemented. In addition to this, we do research in order to demonstrate how the framework may be used.